Southeast Asia: An Introductory History - Osborne, Milton
"Southeast Asia: An introductory history has been the most widely read introduction to the region for over fifteen years and still retains its reputation as a highly readable survey of Southeast Asia's modern history. Clearly written and extensively illustrated with maps, prints and photographs, it has been revised and brought up-to-date for this seventh edition." "While giving attention to the early history of Southeast Asia, the author concentrates on the changes that have taken place since the eighteenth century. He surveys such vital developments as the impact of colonial rule, economic transformations in the nineteenth and twentieth centuries, the emergence and triumph of independence movements and the impact of social change and the pivotal roles played by religion, ethnic-minorities and immigrant groups in the various countries of the region."--BOOK JACKET.